Security Strategy at Indonesia Archipelagic Sea Lane - Hadi Pranoto; Amarulla Octavian (The Republic of Indonesia Defense University, 2015)
This research aims to describe the implementation security strategy of Indonesia Warship Western Command Fleet in Indonesia's archipelagic sea lanes, will be dealing abuses and sea crimes. This research used a qualitative method with descriptive approach, research data from interviews and documents. The results is security strategies Indonesia's archipelagic sea lanes using a choke point control patterns to support the readiness of Indonesia Warship capabilities, which are limited and need to increase surveillance capabilities vessel with technological developments and increased cooperation with agencies to be able to realize its strategy of securing Indonesia's archipelagic sea lanes